Nucula sulcata Bronn 1831 ... - Kiel, Steffen; Sami, Marco; Taviani, Marco (Zenodo, 2023)
Nucula aff. sulcata Bronn, 1831 Fig. 8A–D Material examined ITALY – Tuscany • 3 specs; Le Colline; MSF 1210 (L = 6.2 mm), MSF 1212 (H = 7.3 mm), MSF 2366 • 1 spec.; same collection data as for preceding; NRM Mo 205366 • 1 spec.; Ca’ Cavalmagra; MSF 1311 (L = 10.7 mm). Remarks Nucula sulcata is an extant taxon, common in the European Neogene and Quaternary, its taxonomic history, nomenclature, and distribution was extensively discussed by La Perna (2007). The specimens illustrated here resemble Nucula sulcata in general outline, but with the hinge features obscured, our assignment remains tentative. Lucente & Taviani (2005) recorded a Nucula sp. of comparable dimensions (only a mold) associated with large vesicomyids from Serravallian-aged hydrocarbonimprinted sediments in the Romagna Apennines. Order Solemyida Dall, 1889 Family Solemyidae Gray, 1840 ... : Published as part of Kiel, Steffen, Sami, Marco & Taviani, Marco, 2023, Mollusks (Gastropoda, Bivalvia) from Miocene cold-seep deposits in northern Italy: revisions and additions, pp. 115-160 in European Journal of Taxonomy 910 on pages 138-139, DOI: 10.5852/ejt.2023.910.2365, http://zenodo.org/record/10350702 ...